دور المحـامين المناهضين للاستعمار الفرنسي إبان الثورة الجزائرية - خامس, سامية (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى إبراز دور المحامين الجزائريين والأجانب إبان الثورة الجزائرية، ومدى التزامهم في مناهضة الحرب الاستعمارية في الجزائر طبقا لتعليمات قيادة الثورة الجزائرية، واستجابتهم السريعة للدفاع عن المناضلين المعتقلين. وإبراز دورهم في مجال حقوق الإنسان من خلال التشهير بفظائع الحرب وانتهاكاتها لحقوق المناضلين المضطهدين في سجون الاحتلال، وإنصاف الكفاح المشروع للمناضلين خلال المرافعات في قاعات المحاكم الاستعمارية ، والعراقيل التي اعترضتهم خلال أداء مهنتهم من قبل السلطات القضائية بالتواطؤ مع السلطات العسكرية. This study aims to highlight the role of Algerian and foreign lawyers during the Algerian, and the extent of their commitment to fight against colonial war in Algeria in accordance with the instructions of Algerian revolution leaders, and their prompt response to defend jailed militants. and to highlight also their roles in the field of human rights through denouncing the war atrocities and its violation of persecuted militants rights in occupation prisons, and the role they played to bring justice to the legitimate struggle through pleadings in colonial courts, and the obstacles they encountered in the exercise of their functions and drawn up by the colonial judicial authorities with the complicity of the military authorities.
مقال
Keywords: تعبئة، محامون، الحرب، جاك فرجاس، جميلة بوحيرد; mobilization, lawyers, the war, jacques Verges, djamila Bouhired